Transmission of metallo-β-lactamase-producing Pseudomonas aeruginosa in a nephrology-transplant intensive care unit with potential link to the environment. Issue 1 (January 2016) - Ambrogi, V.; Cavalié, L.; Mantion, B.; Ghiglia, M.-J.; Cointault, O.; Dubois, D.; Prère, M.-F.; Levitzki, N.; Kamar, N.; Malavaud, S.
Summary: Pseudomonas aeruginosa has been recovered in hospitals from many different sources including sinks and taps. Because P. aeruginosa is one of the main agents of nosocomial infections and increasingly resistant to antibiotics, environmental reservoirs in hospital settings are of great concern. We report here on a cluster of five cases of infection by P. aeruginosa expressing VIM carbapenemases (VIM-PA) in a nephrology intensive care unit. Our investigation pointed to transmission of VIM-PA via hands related to a contaminated tap. VIM-PA may be cross-transmitted to other patients if an environmental reservoir exists. Sinks and taps should be well designed and thoroughly cleaned and disinfected, and use of alcohol hand rub should be promoted.